Portable perfusion phantom for quantitative DCE‐MRI of the abdomen. Issue 10 (12th August 2017) - Kim, Harrison; Mousa, Mina; Schexnailder, Patrick; Hergenrother, Robert; Bolding, Mark; Ntsikoussalabongui, Bernard; Thomas, Vinoy; Morgan, Desiree E.
Abstract : Purpose: The aim of this study was to develop a portable perfusion phantom and validate its utility in quantitative dynamic contrast‐enhanced magnetic resonance imaging of the abdomen. Methods: A portable perfusion phantom yielding a reproducible contrast enhancement curve (CEC) was developed. A phantom package including perfusion and static phantoms were imaged simultaneously with each of three healthy human volunteers in two different 3T MR scanners. Look‐up tables correlating reference (known) contrast concentrations with measured ones were created using either the static or perfusion phantom. Contrast maps of image slices showing four organs (liver, spleen, pancreas, and paravertebral muscle) were generated before and after data correction using the look‐up tables. The contrast concentrations at 4.5 min after dosing in each of the four organs were averaged for each volunteer. The mean contrast concentrations (4 organs × 3 volunteers = 12) were compared for the two scanners, and the intra‐class correlation coefficient (ICC) was calculated. Also, the ICC of the mean K trans values between the two scanners was calculated before and after data correction. Results: The repeatability coefficient of CECs of perfusion phantom was higher than 0.997 in all measurements. The ICC of the tissue contrast concentrations between the two scanners was 0.693 before correction, but increased to 0.974 after correction using the look‐up tables (LUTs) of perfusion phantom. However, the ICC was not increased after correction using static phantom (ICC: 0.617). Similarly, the ICC of the K trans values was 0.899 before correction, but increased to 0.996 after correction using perfusion phantom LUTs. The ICC of the K trans values, however, was not increased when static phantom LUTs were used (ICC: 0.866). Conclusions: The perfusion phantom reduced variability in quantitating contrast concentration and K trans values of human abdominal tissues across different MR units, but static phantom did not. The perfusion phantom has the potential to facilitate multi‐institutional clinical trials employing quantitative DCE‐MRI to evaluate various abdominal malignancies.